Aflatoxin in milk and dairy products - Ikins, W.G. (Kansas Agricultural Experiment Station, 2012)
Aflatoxins are toxic compounds that are produced by certain strains of molds, namely, Aspergillus flavus and Aspergillus parasiticus. These molds may invade stressed crops in the field or proliferate in improperly stored feed. Dairy cows are one of the many species of animals that may suffer both long-term and short-term adverse effects from consuming aflatoxin contaminated feed. In addition, dairy cows metabolize the toxin to a slightly different form, a portion of which is secreted into milk and can be consumed by humans.
Keywords: Dairy; Aflatoxin; Milk; Dairy products